THE USE OF PRE-QUESTION STRATEGY IN IMPROVING STUDENTS’ READING ACHIEVEMENT - Sukma, Linda Melati; Mortini, Asti Veto; Noviati; Nur Aisyah; Lim Wei Jie (Universitas PGRI Palembang, 2025)
Reading proficiency is an essential skill that students must develop, as challenges in this area can significantly impede their ability to absorb and process information. This research aimed to determine whether the application of the pre-question strategy had a statistically significant impact on the reading achievement of tenth-grade students at SMA PGRI 2 Palembang compared to those who were not exposed to this instructional method. The study utilized a quasi-experimental design, dividing one class into two distinct groups: an experimental group and a control group. The population consisted of tenth-grade students, and the sample included a single class, selected through cluster sampling, which was further divided into experimental and control subgroups. Data were collected through a reading test. The analysis revealed that the obtained t-value was 15.180, which exceeded the critical t-value of 1.691 at a significance level of 0.05 with 34 degrees of freedom. This indicates a statistically significant difference between the two groups. Based on these findings, it is recommended that English teachers incorporate the pre-question strategy into their instructional practices, particularly in reading instruction, as it appears to facilitate students’ comprehension of the text. Furthermore, this strategy has the potential to boost students’ confidence when engaging with reading materials.